-3(-6+2x)=9

Simple and best practice solution for -3(-6+2x)=9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(-6+2x)=9 equation:


Simplifying
-3(-6 + 2x) = 9
(-6 * -3 + 2x * -3) = 9
(18 + -6x) = 9

Solving
18 + -6x = 9

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-18' to each side of the equation.
18 + -18 + -6x = 9 + -18

Combine like terms: 18 + -18 = 0
0 + -6x = 9 + -18
-6x = 9 + -18

Combine like terms: 9 + -18 = -9
-6x = -9

Divide each side by '-6'.
x = 1.5

Simplifying
x = 1.5

See similar equations:

| 0.125(3y+2)=4(2y+0.5)+2 | | 2x+28=10+6x | | 7x+2=4x-3 | | 7-9x=2x+1 | | 4x+x=2x | | 7x+3(4x+3)=161 | | 20=7x+5-4x | | (6ab-abc)+(ab+6abc)= | | 180=4y+20 | | a-(24/11)=(49/22)-(13/11) | | 7x-4=2x-5 | | -2(2z+7)-4(4z-7)-18z= | | 3x+7(2x-11)=76 | | -5=32-3b | | z=10y | | 180=4x-16 | | 7p=12 | | 0.3x+y=2 | | 15=2(x+7)-14 | | -5x-23=93 | | 7(4-2x)=-7x | | (18p-19q)+(10p-14q)= | | 3a+10=3a | | (x+4)9-3=(11+3x)+x | | 4(8+y)=22 | | 3x+7(5x-13)=175 | | x=3(y)+1 | | (x-4+2i)(x+4+2i)=0 | | 2/7+a=(4/3)+(6/21) | | 12p=7 | | 7x-2(3+4x)=18 | | 40-6x=110-26x |

Equations solver categories